The concept of building control for certain components of the system for training handball players - Tyshchenko, V.; Ilisenchuk, G.; Odynets, T.; Cherednichenko, I.; Lytvynenko, O.; Boretska, N.; Semeryk, Z. (Journal of Physical Education and Sport, 2019)
The purpose of the research- to find developed similarityin concepts of training systems control for high qualified handball playersand demands of their training and competitive activity. The methodology of the work.The expert assessment was conducted for direct participants, such as trainers of the training and competitive process of Super League Ukrainian teams, "Motor" and "ZTR". Results. According to the generalized estimations of experts, which we interpret as a holistic assessment of control system in training and competitive activity for highly qualified handball teams in the annual training macrocycle 2017-2018.It has been defined by its compliance with the essential task of the training system. Most assessments of the criteria were within full compliance with their requirements. Thus, the highest scores recorded for the purpose and validity of the criteria (by 3.78 and 3.81 points); presentation of information and coordination of control components (by 3.74 and 3.67 points); costs (by 3.59 points); completeness of the information (by 3.56 points); the value of information (by 3.41 points); determinism (by 3.19 points) and speed of decision (by 3.11 points). Another two assessments of criteria were closer to the high level and accounted for the continuity of the content of information and the frequency of control 2.96 and 2.78 points. Conclusions. The confirmed effectiveness of the development on the basis of our concept, control system of training and competitive activity of highly qualified handball teams in the annual preparation of the macrocycles. It has been recommended to use separate scientific and methodological guidelines, the concept of control components, as well as those that are based on a theoretical and practical level means and methods of control in long-term training for highly qualified handball teams.